Analysis of on-line tutorials of departments of physical education of institutes of higher of mountain type - Батечко (Batechko D.) Дмитро Петрович (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Maintenance of on-line tutorials and work of departments of physical education of higher educational establishments of mountain type is analysed. It is well-proven that the program answers the basic criteria of forming of on-line tutorials on physical education and "physical education" assists to development of discipline in higher educational establishments, however attention not enough is spared the professionally-applied physical preparation. This analysis enables to define directions of perfection of the system of physical education of specialists in the institute of higher of mountain type. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>